2018
DOI: 10.3390/vetsci5030067
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Rabies in the Middle East—Beyond Neglect

Abstract: Rabies is a neglected but preventable viral zoonosis that poses a substantial threat to public health. In this regard, a global program has been initiated for the elimination of human rabies caused by rabid dogs through the mass vaccination of canine populations. Geographic areas vary greatly towards attainment of this objective. For example, while dog-mediated and wildlife rabies have been largely controlled in major parts of the Americas and Western Europe, the Middle East still grapples with human rabies tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Countries in the Middle East are hotspots for emerging and re-emerging infectious diseases, partly because of their ecological, cultural, socioeconomic, and political diversity, but also due to the unrest, conflict, and wars in this region [ 18 , 19 ]. The lack of relevant information on infectious diseases, their sources, and their diversity is a major drawback for public health studies in this area, possibly misguiding both civilians and governments in their attempts at mitigation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Countries in the Middle East are hotspots for emerging and re-emerging infectious diseases, partly because of their ecological, cultural, socioeconomic, and political diversity, but also due to the unrest, conflict, and wars in this region [ 18 , 19 ]. The lack of relevant information on infectious diseases, their sources, and their diversity is a major drawback for public health studies in this area, possibly misguiding both civilians and governments in their attempts at mitigation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the risk run by humans of being bitten by a rabid wildlife species is small [ 64 ], this is intuitively substantially higher when it comes to domestic animals such as cats. Through this way, even historically rabies-free areas—particularly when involving migratory bat species [ 65 ]—and urban or rural environments [ 66 , 67 , 68 ] may be affected. For instance, in Brazil, in 2008–2016, only 1.4% cases of people bitten by animals concerned wildlife vs. 94% of bites by dogs and cats [ 64 ].…”
Section: State Of Art Of Bat–cat Exchange Of Pathogensmentioning
confidence: 99%
“…No report on rodent helminths was available from Bahrain, Jordan, Lebanon, Oman, United Arab Emirates, and Yemen. Cestodes were the most frequently reported (50 articles) helminths in the Middle Eastern rodents, followed by nematodes (49), and trematodes (14). All 65 studies reported at least 9628 rodents (47% females and 53% males).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Cultural diversity, weak economic policy, poor governance, rapid population growth, low educational structure, gender discrimination, underdeveloped infrastructure, and war and conflict have turned the region into a hot spot for many emerging and re-emerging diseases, including rodent-borne parasitic infections [ 9 , 12 , 13 ]. In the past, rodent-borne infections have led to multiple instances of a fatal epidemic, in part due to a lack of relevant information available on the subject, which makes it difficult to maintain public health sustainability [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%